Low-cost platform for the evaluation of single phase electromagnetic phenomena of power quality according to the IEEE 1159 standard (2015)
This paper presents the development of a data acquisition system and the evaluation of the electromagnetic phenomena associated with power quality according to the IEEE Standard 1159-1992 and applied to the particular case of single-phase electrical power systems. The evaluation software is implemented in the Labview® professional software using a NI 6009 USB board of the National Instrument® as acquisition device. The hardware implementation of the sensors was shown. Also the development of the algorithm and the design of a graphical user interface for viewing of the voltage and current waveforms, spectra, frequency and the power quality disturbances such as sags, swells, undervoltage, overvoltage, so on. Likewise, at the end a concise analysis of costs is presented to show that the developed system has a lower price to current solutions that are available in the market. Finally a study case was shown.